Identification of the Potential of Taro (Araceae) as a Source of Animal Feed in the Central Mahakam Region - Safitri, Apdila; Indana, Khoiru; Dhonanto, Donny; Kurniadinata, Odit Ferry; Pujowati, Penny; Nugroho, Agung Enggal (CV. Komunitas Dunia Peternakan, 2024)
The Central Mahakam region is a peat swamp ecosystem with cascade lakes in East Kutai, West Kutai, and Kutai Kartanegara. The region has abundant potential for taro plants (Araceae). The community uses taro only for food and is not used as a feed ingredient. This research aims to identify the types and potential of taro for use as animal feed. Observations were conducted in two villages in the Central Mahakam region: Batuq and Tuana Tuha Villages, Muara Muntai District, Kutai Kartanegara Regency. Taro samples will be taken based on habitat and then subjected to proximate analysis to determine chemical content. The method used in this research was exploratory. The results of identifying the types of taro in Batuq Village showed four types of taro, while there were two types in Tuana Tuha Village. The taro-growing habitat for the Colocasia sp species is terrestrial/semi-terrestrial, while the Xanthosoma sagittifolium species grows terrestrially. The part of taro that can be used as food is in the form of leaves. The chemical content of taro leaves (Colocasia esculenta) dry weight is 90.39%, crude protein is 4.62%, Ash is 4.51%, crude fat is 1.01%, and crude fiber is 3.86%. The Xanthosoma sagittifolium type contains 90.52% dry weight, 4.47% crude protein, 4.39% ash, 1.06% crude fat, and 3.56% crude fiber. There are six types of taro found in the Central Mahakam region, and they have the potential to be an alternative food source based on their chemical content.